Antibacterial activity of Zingiber officinale roscoe extract as a potential root canal irrigation solution against Enterococcus faecalis - Azhar, Rodiyah; Julianti, Elin; Natasasmita, Setiawan; Dharsono, Hendra Dian Adhita (Padjadjaran Journal of Dentistry, 2018)
Introduction: This study was aimed to determine and formulate antibacterial activity of Zingiber Officinale Roscoe (Z. officinale) extract against Enterococcus faecalis (E. faecalis) as a potential irrigating solution which is easily available and cost-effective. Methods: Â Extract of Z. officinale Roscoe was yielded through soxhlet technique. Samples divided into two groups, i.e., the extract of Z. officinale Roscoe and chlorhexidine 2% as a control. The antimicrobial activity was observed using the diffuse agar method. Minimum inhibitory concentration (MIC) was determined by serial microdilution method, and minimum bactericidal concentration (MBC) was determined by cultured samples in blood agar. Data were analysed using ANOVA and Kruskal-Wallis test. Results: Extract of Zingiber officinale Roscoe has antimicrobial activity against E. faecalis with the MBC of 15.625 mg/mL. (p<0,05). Conclusion: Extract of Zingiber officinale Roscoe have shown antibacterial activity againstÂ E. faecalis and can be further developed as a potential root canal irrigation solution.